Cordialin A isolated from Varronia curassavica Jacq. loaded in nanoemulsion as potential cytotoxic agent on human cervical tumor cells - Baveloni, Franciele Garcia [UNESP]; Scardelato, Juhan Augusto [UNESP]; Carvalho, Flávio Alexandre [UNESP]; Paino, Ieda Maria Martinez [UNESP]; Medina-Alarcón, Kaila Petrolina [UNESP]; Pereira-da-Silva, Marcelo A.; Chorilli, Marlus [UNESP]; dos Santos, André Gonzaga [UNESP]; Soares, Christiane Pienna [UNESP] (Springer Nature, 2024)
Cervical cancer is the fourth most common cancer in women worldwide. Most cases of cervical cancer are caused by the human papillomavirus. Triterpenes, which are secondary metabolites of plants, are known for their antitumor activity. Cordialin A, isolated from the ethanolic extract of Varronia curassavica Jacq. leaves, shows potential for cervical cancer therapy. Cordialin A is a low-polarity molecule, and its incorporation into nanoemulsion systems (NEs) can enhance its cytotoxic effects on tumor cells. The NE, composed of cholesterol, phosphate buffer, the surfactant polyoxyethylene 20-cetyl ether, and soy phosphatidylcholine, was used to encapsulate cordialin A. The droplets of the cordialin A-loaded NE measured 107 nm in size, with a particle distribution index of 0.214, and a ζ-potential of − 20 mV. Cytotoxicity assays showed that the concentration required to inhibit 50% of cell viability was more potent in cordialin A-loaded NE compared to free cordialin A against cervical tumor cell lines. Marked morphological changes indicative of apoptosis and necrosis were observed in cells after 12 h of exposure to both cordialin A and cordialin A-loaded NE. These results suggest that cordialin A-loaded NE has potential for use in the treatment of cervical cancer. Graphical abstract: Cordialin A isolated from Varronia curassavica Jacq. loaded in nanoemulsion as potential cytotoxic agent on human cervical tumor cells (Figure presented.)
Keywords: Cervical cancer cells; Cordialin A; Cytotoxicity; Nanoemulsion